2021
DOI: 10.3389/fimmu.2021.749291
|View full text |Cite
|
Sign up to set email alerts
|

Effects of β-Blockers on the Sympathetic and Cytokines Storms in Covid-19

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a causative virus in the development of coronavirus disease 2019 (Covid-19) pandemic. Respiratory manifestations of SARS-CoV-2 infection such as acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) leads to hypoxia, oxidative stress, and sympatho-activation and in severe cases leads to sympathetic storm (SS). On the other hand, an exaggerated immune response to the SARS-CoV-2 invasion may lead to uncontrolled release of pro-infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 114 publications
0
47
0
Order By: Relevance
“…In its clinical perspective, IVN might be a pioneer drug in attenuating cardiotoxicity, mainly in patients with heart failure, arrhythmias, and malignancies treated by DXR. It has been shown that unlike β-blockers, IVN does not decrease ventricular force (Su et al 2020 ; Al-Kuraishy et al 2021b , 2022c , d ; Lawal et al 2021 ) and can also reduce COVID-19-induced cardiovascular complications due to its anti-inflammatory and antioxidant properties (Al-Kuraishy et al 2021c , 2022e ; Batiha et al 2021 , 2022 ). In addition, IVN facilitates a pleiotropic cardioprotective effect against isoproterenol-induced acute cardiac injury by increasing the ventricular fibrillation threshold (Simko et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In its clinical perspective, IVN might be a pioneer drug in attenuating cardiotoxicity, mainly in patients with heart failure, arrhythmias, and malignancies treated by DXR. It has been shown that unlike β-blockers, IVN does not decrease ventricular force (Su et al 2020 ; Al-Kuraishy et al 2021b , 2022c , d ; Lawal et al 2021 ) and can also reduce COVID-19-induced cardiovascular complications due to its anti-inflammatory and antioxidant properties (Al-Kuraishy et al 2021c , 2022e ; Batiha et al 2021 , 2022 ). In addition, IVN facilitates a pleiotropic cardioprotective effect against isoproterenol-induced acute cardiac injury by increasing the ventricular fibrillation threshold (Simko et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, oxidative stress is linked with the progression of SARS-CoV-2 infection and COVID-19 severity due to ROS generation, mitochondrial dysfunction, dysregulation of RAS, and reduction of endogenous antioxidant capacity (Cecchini and Cecchini 2020 ). In turn, oxidative stress triggers release of pro-inflammatory cytokines via activation of inflammatory signaling pathways including nuclear factor kappa B (NF-κB), nod-like receptor pyrin 3 receptor (NLRP3) inflammasome and p38 mitogen activated protein kinase (p38MAPK) (Al-Kuraishy et al 2022a ; Mostafa-Hedeab et al 2022 ; Al-Kuraishy et al 2021g ). Pro-inflammatory cytokines and activated inflammatory signaling pathways interacted together in the induction of oxidative stress in SARS-CoV-2 infection (Al-Kuraishy et al 2022b ).…”
Section: Citicoline Oxidative Stress and Hyperinflammationmentioning
confidence: 99%
“…A retrospective analysis demonstrated that the use of alpha-1 adrenergic receptor antagonists reduced COVID-19 in-hospital mortality by 77% (odds ratio (OR): 0.23; 95% CI: 0.03-0.94; p = 0.028) [ 56 ], while beta-blockers reduced the inflammatory response that led to cytokine storms in COVID-19 [ 57 ]. In addition, SARS-CoV-2 mRNA vaccination has been followed by multiple cases of Takotsubo cardiomyopathy [ 58 ], a syndrome triggered by excessive catecholamine release and activity [ 59 ].…”
Section: Reviewmentioning
confidence: 99%